Genome of a Novel Isolate of Paracoccus denitrificans Capable of Degrading N,N-Dimethylformamide - Siddavattam, D.; Karegoudar, T.B.; Mudde, S.K.; Kumar, N.; Baddam, R.; Avasthi, T.S.; Ahmed, N. (American Society for Microbiology, 2011)
The bacterial genus Paracoccus is comprised of metabolically versatile organisms having diverse degradative capabilities and potential industrial and environmental applications for bioremediation in particular. We report a de novo-assembled sequence and annotation of the genome of a novel isolate of Paracoccus denitrificans originally sourced from coal mine tailings in India. The isolate was capable of utilizing N,N-dimethylformamide (DMF) as a source of carbon and nitrogen and therefore holds potential for bioremediation and mineralization of industrial pollutants. The genome sequence and biological circuitry revealed thereupon will be invaluable in understanding the metabolic capabilities, functioning, and evolution of this important bacterial organism.